Approaches for the Accounting Profession-Based Development of Skills and Abilities for the Accountants Working in Accounting Offices in Southern Thailand - Yohmad, Saranya; Prabrat, Somchai (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research encompasses three main purposes: 1) to study the levels of knowledge potential, skills, and code of professional ethics of accountants in the accounting firms in Southern Thailand, 2) to compare the levels of knowledge potential, skills, and code of professional ethics of accountants with different personal details and knowledge management of the modern accounting in the accounting firms in Southern Thailand, and3) to propose guidelines for the development of knowledge potential, skills, and code of accounting professional ethics of accountants in the accounting firms in Southern Thailand. The sample consists of 159 full-time accountants working for the accounting firms across Southern Thailand. The outcomes are shown to be as follows: Accountants have professional potential, knowledge, and skills at a high level, while the code of accounting professional ethics is at the highest level. Accountants have their opinions towards the knowledge management of modern accounting at a high level, both overall and individually. Planning, application, accumulation, and exchanges are proposed for the management of accounting knowledge. Accountants have been in their firms for a varying number of years and have different potential within the accounting profession at a statistically significant rate of .05. Accountants with different levels of knowledge management of modern accounting exist within both the low-moderate group and high- highest group, having a different average of potential, knowledge, skills, and code of accounting professional ethics statistically significant at .01. Accountants of different genders, ages, levels of education, current positions, and years’ of experience have no different potential in the accounting profession, at a statistically significant rate of 01.